Adaptive mechanism of stress tolerance in Urochondra (grass halophyte) using roots study - LATA, CHARU; SONI, SHOBHA; KUMAR, NARESH; KUMAR, ASHWANI; POOJA, POOJA; MANN, ANITA; RANI, SULEKHA (The Indian Journal of Agricultural Sciences, 2019)
An experiment was conducted on Urochondra setulosa (grass halophyte) to explore its survival mechanism under stress conditions. For this, different treatments of salinity/sodicity (pH ~ 9.5, pH ~ 10, ECe ~ 30 dS/m, ECe ~ 40 dS/m and ECe ~ 50 dS/m) were created in micro-plots. Roots are the primary structure that first senses the negative effects of salt stress. So, roots were selected to study the tolerance mechanism. Salinity stress caused higher Na+ accumulation and less reduction in K+ content in comparison to sodic stress. Roots accumulated 4.57 folds higher proline at ECe ~ 50 dS/m, whereas under pH ~ 10.0, 3.11 fold higher accumulations than the control roots were observed. Higher reduction in protein content was observed under sodicity stress than salinity stress. In control roots, a total of 26 polypeptide bands were expressed ranging from 12.43 kDa to 81.3 kDa. Under high salinity stress, number of polypeptide bands increased to 31 at ECe ~ 50 dS/m that might be responsible for their survival and growth while sodic stress led to disappearance of more number of polypeptides with a total number of 23 polypeptides at pH ~ 10.0. Interestingly, it was also found that sodic stress had higher damaging affect on Urochondra metabolism in comparison to salinity stress which makes it salinity tolerant grass.